(untitled) - Silverman, Jerald (Boca Raton, 2009)
This book is a good informational resource for any new manager to the field of laboratory management. The information is presented in a way that will keep your interest and stimulate you to think how it can benefit you and the facility in which you work
Keywords: Biological laboratories,Laboratories,Laboratory Animal Science,Thí nghiệm sinh học,Phòng thí nghiệm,Thí nghiệm động vật khoa học; Management,Organization & administration,Quản lý,Tổ chức và quản lý